An Evaluation of Lifestyle Health Coaching Programs Using Trained Health Coaches and Evidence-Based Curricula at 6 Months Over 6 Years. Issue 6 (July 2019) - Budzowski, Amanda R.; Parkinson, Michael D.; Silfee, Valerie J.
Purpose: Describe health plan member-level participation, completion, and 6-month outcomes for 5 lifestyle health coaching programs offered by an integrated delivery and financing system (IDFS) over 6 years. Design: Case series study of 5 lifestyle programs with 180-day follow-up. Setting: Large Western PA integrated delivery and financing system (IDFS) deployed multiple coaching modalities for diverse insurance-member enrolled population. Participants: A total of 14 591 health plan members choosing a lifestyle health coaching program. Intervention: Evidence- and curriculum-based lifestyle health coaching programs delivered by 1 of 4 interactive modalities. Measures: A single metric was used as an overall indicator of clinical success for each program. Success measures include a ≥5% reduction of self-reported baseline weight, meeting physical activity guidelines, and 7-day point prevalence abstinence from tobacco. For stress and nutrition, where no single target measure exists, a metric was created that represented a net improvement across all key outcomes measured. Analysis: The proportion of members meeting target outcomes were calculated and described across all time points and modalities. Results: At 180 days, 77% of enrolled members reported reduced stress, 7% quit tobacco, 50.5% met physical activity guidelines, 65.2% improved nutrition, and 44.2% lost 5% or more of baseline weight. Conclusion: This evaluation describes the real-world effectiveness of evidence- and curriculum-based lifestyle improvement programs delivered by trained health coaches to a diverse health plan member population.